Factors Driving Tax Compliance Among SMEs: A Systematic Literature Review - Muhammad Wildan Basri; Diah Ilmi Rizqiana (Jurnal Bisnis dan Kewirausahaan, 2026)
Small and Medium Enterprises tax compliance is a critical issue in efforts to broaden the tax base and increase government revenue; however, the literature reveals variations in determining factors and a concentration of studies in developing countries. This systematic literature review aims to summarize the empirical evidence regarding the factors influencing SME tax compliance, as well as policy implications and directions for further research. The study followed the PRISMA guidelines with a search in the Scopus database for the period 2016 to 2025, yielding 19 articles that met the inclusion criteria. The selection process included identification, screening, eligibility assessment, and inclusion; analysis was conducted descriptively and thematically to extract constructs, methods, and key findings. The review results identified five key factors that consistently influence SME tax compliance: awareness of tax obligations, characteristics of accounting practices, complexity of tax policies, availability of tax information, and the probability of audits. This study underscores the importance of tax information and provides integrated evidence for policymakers.